Retail stability of three beef muscles from grass-, legume-, and feedlot-finished cattle. (6th April 2018) - Legako, Jerrad F; Cramer, Traci; Yardley, Krista; Murphy, Talya J; Gardner, ToniRae; Chail, Arkopriya; Pitcher, Lance R; MacAdam, Jennifer W
Abstract: This study aimed to determine the influence of finishing diet on beef appearance and lipid oxidation of three beef muscles. A total of 18 Angus steers were selected from three diet treatments: grass-finished (USUGrass ), legume-finished (USUBFT ), and grain-finished (USUGrain ). After processing, longissimus thoracis (LT ), triceps brachii (TB ), and gluteus medius (GM ) steaks were evaluated over a 7-d display period. A muscle × diet interaction was observed for instrumental lightness (L*) and redness (a*) ( P ≤ 0.001). Within each combination, USUGrass was considered darker with lower ( P < 0.05) L* compared with USUGrain. For USUBFT, L* was similar to USUGrain for the TB and LT, while the L* of USUBFT and USUGrain GM differed ( P < 0.05). In terms of redness, LT a* values were elevated ( P < 0.05) in USUGrass compared with USUBFT and USUGrain. For GM steaks, a* of USUBFT and USUGrass were each greater ( P < 0.05) than USUGrain. Surface a* of TB steaks were greatest ( P < 0.05) for USUGrass followed by USUBFT, and with USUGrain, being lowest ( P < 0.05). An overall increase in L* was observed throughout display dependent on diet ( P = 0.013). During display, USUGrain steaks had the greatest ( P < 0.05) L* followed by USUBFT and USUGrass. Additionally, a day × muscle interaction was observed for a* ( P = 0.009). Initially, TB steaks had the greatest ( P < 0.05) a* values. However, at day 3, a* values were similar ( P > 0.05) among muscles. Visual color scores were in agreement with loss of redness (a*) during display, dependent on diet and muscle type ( P < 0.001). Similarly, a day × diet × muscle interaction was observed for visual discoloration ( P < 0.001). Day and diet interacted to influence thiobarbituric acid reactive substances (TBARS ) ( P < 0.001). Initial values did not differ ( P > 0.05) between USUGrain and USUBFT; however, USUGrass had lower initial ( P < 0.05) TBARS than both USUGrain and USUBFT. At days 3 and 7, TBARS were greatest ( P < 0.05) in USUGrain steaks, followed by USUBFT, which was greater ( P < 0.05) than USUGrass. A diet × muscle interaction was observed for 10 volatile compounds originating from lipid degradation ( P ≤ 0.013). These compounds were less ( P < 0.05) abundant in USUGrass compared to TB or GM of USUGrain. This study determined grass-finished beef to have a darker more red color and less lipid oxidation in multiple muscles. Possible mechanisms for this may include an increase in endogenous antioxidants in grass-finished beef.